Wideband and Low-Profile Array of Tightly Coupled Dipole Subarrays - Seongjung Kim; Sangwook Nam (Journal of Electromagnetic Engineering and Science)
This letter introduces a novel wideband, low profile, tightly coupled dipole subarray for wireless communication systems. The proposed subarray, composed of 3 × 3 unit elements, offers a planar structure with high aperture efficiency. The unit element is a bow-tie-shaped tightly coupled dipole antenna covered by a frequency-selective surface for wideband operation. Using power dividers with quarter-wave transformers, the proposed subarray achieved an impressive impedance-matching bandwidth of 28.6–41.6 GHz (37.8%). This wideband performance was maintained in a 4 × 4 array configuration as well. The antenna’s low-profile design (0.08λc) and high aperture efficiency (77.2%) set it apart from existing wideband patch array antennas, making it a promising candidate for future wireless communication applications.